Impact of the lipid–inflammation axis on endometriosis risk: a multicenter case–control study using mediation analysis - Duan, Yanan; Kong, Fanmao; Ding, Zhaoxia; Peng, Yiqing; Chen, Aiping; Yao, Yushuang (Frontiers in Endocrinology, 2025)
BackgroundEndometriosis (EM) is often accompanied by dyslipidemia, but the causal relationship between dyslipidemia and inflammation remains unclear. This study aimed to explore the association between the lipid-inflammation axis and EM risk and to quantify the mediating role of the systemic immune-inflammation index (SII).MethodsA total of 357 EM cases and 3134 controls were included. Blood lipids and SII were assessed using logistic regression, generalized additive models (GAM), and bootstrap mediation analysis. Least absolute shrinkage and selection operator (LASSO) modeling was applied, and the model was further evaluated in an external cohort.ResultsFor each 1 mmol/L decrease in high-density lipoprotein cholesterol (HDL-C), EM risk increased by 55%. Conversely, each 1 mmol/L increase in triglycerides (TG) and each one-unit increase in the non-HDL-cholesterol to HDL-cholesterol ratio (NHHR) were associated with 21% and 54% higher risk, respectively. Mediation analysis suggested that 88-103% of the effects of HDL-C, TG, and NHHR on EM were mediated through SII. A nomogram incorporating these variables achieved an external validation area under the curve (AUC) of 0.93, indicating strong statistical discrimination.ConclusionDyslipidemia may contribute to the development of EM through systemic inflammation, with SII serving as a potential intermediate marker. These findings suggest the potential value of integrating lipid regulation and anti-inflammatory strategies for EM prevention, although further clinical validation is warranted.